The Effect of Questioning Technique in Pre-Writing Stage Toward Students’ Writing Ability - Herayati Herayati (Journal on Education, 2020)
One of the requirements in teaching English at Junior High Schools is the students are required to get better result in writing kinds of text. However, the fact showed that the students still faced problems in writing. Those problems can be caused because of not all stages of writing process are done. Specifically, the students did not go through and use a certain technique on prewriting stage, thus, they faced problems in expressing their ideas, organizing ideas, and developing good paragraph to produce a text type. Therefore, the researcher conducted an experimental reserach. The purpose of this reserach is to find out whether or not the effect of using questioning technique in pre writing stage toward students’ writing ability. Based research result, it was found that there was significant effect of using questioning technique toward students’ writing ability. Thus, the researcher suggests the English teachers and the students to apply questioning technique in writing process.